Molecular and clinical characteristics of carbapenem-resistant Enterobacteriaceae isolates collected at a tertiary hospital in northern China. (25th June 2022) - Wang, Hua; Yan, Zhi; Mu, Lan; Gao, Xiang-Yu; Li, Jia-Ying; Hu, Zhi-De; Wang, Jun-Rui; Zheng, Wen-Qi
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) represent a severe public health problem. Methods: In a tertiary hospital in northern China, 169 non-duplicated clinical CRE strains were analyzed by species identification, in vitro antibiotics sensitivity test, carbapenemase gene detection and genetic sequence typing. Results: The CRE strains showed high resistance to most clinical antimicrobials. Enterobacter cloacae and Escherichia coli isolates mainly carried blaNDM, and Klebsiella pneumoniae isolates mainly carried blakpc . ST11 was the most common type in Klebsiella pneumoniae, and ST70 was the new emerging sequence type (ST) in Enterobacter cloacae . Conclusions: The CRE strains isolated in northern China showed multidrug-resistant phenotypes, and the new emergence of ST70 Enterobacter cloacae should be closely supervised.